Answer:
Part 1) No
Part 2) Option 4.
![f^(-1)(x)=-(1)/(3)x+3](https://img.qammunity.org/2020/formulas/mathematics/high-school/72qw2u4cm1qkdulqtv8njt1t7b1auzd6j9.png)
part 3)
![f^(-1)(9)=4](https://img.qammunity.org/2020/formulas/mathematics/high-school/p1zeiczgsvp7yb5tm936lkr1e5wa7lkyn7.png)
Explanation:
Part 1) we have
![f(x)=8x-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/ickahjqywisiz729y03j1t60cwgt4hobfq.png)
Find the inverse of f(x) and then compare with g(x)
Let
y=f(x)
![y=8x-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/zbdn9gqte9vax38vah8ov58b03dlk28rkl.png)
Exchange the variables x for y and y for x
![x=8y-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/w5igfncguvbykf9ljt7h935ucqp20cfsz6.png)
Isolate the variable y
![8y=(x+3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/v7sij0xulz8onba30ptlttvxwmg7gkrxd2.png)
![y=(x+3)/8](https://img.qammunity.org/2020/formulas/mathematics/high-school/qg12vj68c75l8l8cvsse58auqfbo48kcnr.png)
Let
![f^(-1)(x)=y](https://img.qammunity.org/2020/formulas/mathematics/high-school/3rn8d367xlr8lwqvsqen54z1k5l0mbczf6.png)
![f^(-1)(x)=(x+3)/8](https://img.qammunity.org/2020/formulas/mathematics/high-school/h9rfrrbj77nt99ujacm75lhyiu015xzirw.png)
therefore
the functions f(x) and g(x) are not inverses of each other
Part 2) we have
![f(x)=-3x+9](https://img.qammunity.org/2020/formulas/mathematics/high-school/vj0r9u096bnle7id80xoaeu9veqq5q3le1.png)
Let
y=f(x)
![y=-3x+9](https://img.qammunity.org/2020/formulas/mathematics/high-school/prk2npgkox7o1v0x7gyta00cdoff8p3w54.png)
Exchange the variables x for y and y for x
![x=-3y+9](https://img.qammunity.org/2020/formulas/mathematics/high-school/xumeiohg8pxxc7mxbp89zlogxu7knmexu2.png)
Isolate the variable y
![3y=-x+9](https://img.qammunity.org/2020/formulas/mathematics/high-school/6mtjppvinq2bwv1qoz2trwvu7m2xh5mlz0.png)
![y=(-x+9)/3](https://img.qammunity.org/2020/formulas/mathematics/high-school/g2ffx3qf26nrjnkw4j67xwna848cdmgo5w.png)
Let
![f^(-1)(x)=y](https://img.qammunity.org/2020/formulas/mathematics/high-school/3rn8d367xlr8lwqvsqen54z1k5l0mbczf6.png)
![f^(-1)(x)=(-x+9)/3](https://img.qammunity.org/2020/formulas/mathematics/high-school/kc58zrvf5253l4g7fgk66ksbn0gq417406.png)
![f^(-1)(x)=-(1)/(3)x+3](https://img.qammunity.org/2020/formulas/mathematics/high-school/72qw2u4cm1qkdulqtv8njt1t7b1auzd6j9.png)
Part 3) we know that
For
,
![f(x)=9](https://img.qammunity.org/2020/formulas/mathematics/high-school/bse4lrrrbyfv802a0acfslpbp72557phic.png)
so
For
,
![f^(-1)(9)=4](https://img.qammunity.org/2020/formulas/mathematics/high-school/p1zeiczgsvp7yb5tm936lkr1e5wa7lkyn7.png)